2015
DOI: 10.5397/cise.2015.18.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Classic Floating Elbow in Adults: A Case Series

Abstract: Background: The aim of this study was to assess demographics, clinical outcomes, and complications of classic floating elbow in adults. Methods: Six patients with ipsilateral diaphyseal fractures of the humerus, radius, and ulna were reviewed retrospectively. All patients were treated operatively and available for follow-up at a minimum of 1 year after surgery. The average age of the patients was 45.2 years (22−64 years) and the average follow-up period was 37.0 months (14−103 months). They were evaluated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The Classic Floating Elbow injuries and variants are uncommon injuries that have been reported in both children and Adults [1,2,3] . Stanistiki and Micheli [3] in 1980 first used the term "floating Elbow" to describe the injury pattern of ipsilateral supracondylar humerus and forearm fractures that create an unstable intermediate articulation in children.…”
Section: Discussionmentioning
confidence: 99%
“…The Classic Floating Elbow injuries and variants are uncommon injuries that have been reported in both children and Adults [1,2,3] . Stanistiki and Micheli [3] in 1980 first used the term "floating Elbow" to describe the injury pattern of ipsilateral supracondylar humerus and forearm fractures that create an unstable intermediate articulation in children.…”
Section: Discussionmentioning
confidence: 99%
“…9 Floating elbows occur as a result of high energy trauma, sometimes involving soft tissue and / or neuro-vascular injury. [3][4][5][6][7][8][9][10] Considering the site of injury, the left thoracic limb was involved 3 times and the right thoracic limb 1 time in our study. The predominance of left hemisphere has been found in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Radial nerve paralysis during humeral shaft fractures has been reported in different studies. [3][4][5][6][7][8][9] Considering the prognosis, we noted a case of elbow stiffness and 1 case of aseptic non-union of the radius, associated with a stiffness of the elbow and a limitation of the prono-supination. Other authors have observed the same complications of fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations